2015
DOI: 10.12930/nacada-14-019
|View full text |Cite
|
Sign up to set email alerts
|

Advising as Servant Leadership: Investigating Student Satisfaction

Abstract: Student satisfaction with advising is positively linked to first-year student retention and sophomore persistence to their senior year. However, inconsistencies in the advising literature confound conclusions about the most effective advising approach to elicit student satisfaction. Positive links between the servant leadership approach and advising behaviors have been shown, but student satisfaction remains unexamined. We investigate student satisfaction with servant leadership–based advising. Utilizing hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Three of these behaviors (altruistic calling, wisdom, and persuasive mapping) strongly predicted student satisfaction in combination. These findings provided evidence consistent with the current servant leadership literature, according to which levels of student satisfaction increased when The Relationship Between Instructor Servant Leadership Behaviors and Satisfaction with Instructors in an Online Setting instructors exhibited servant leadership behaviors in traditional, hybrid, or online classroom settings (Ali & Ahmad, 2011;Jacobs, 2011;Huber, 2014;Paul & Fitzpatrick, 2015;Setliff, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Three of these behaviors (altruistic calling, wisdom, and persuasive mapping) strongly predicted student satisfaction in combination. These findings provided evidence consistent with the current servant leadership literature, according to which levels of student satisfaction increased when The Relationship Between Instructor Servant Leadership Behaviors and Satisfaction with Instructors in an Online Setting instructors exhibited servant leadership behaviors in traditional, hybrid, or online classroom settings (Ali & Ahmad, 2011;Jacobs, 2011;Huber, 2014;Paul & Fitzpatrick, 2015;Setliff, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…There is a need to recapture the vision and passion that ignited the early excitement about becoming servants in the field of education (Guillaume, Honeycutt, & Savage-Austin, 2013;Letizia, 2014;Shaw & Newton, 2014). This leadership gap in higher education can be filled by a leadership style that will transform educational institutions and thus restore the public confidence in higher education, foster long-term commitments, and nurture a work environment in which people thrive as they provide service to others (Letizia, 2014;Noland & Richards, 2015;Paul & Fitzpatrick, 2015;Shaw & Newton, 2014;Wheeler, 2012). Servant leadership is that kind of leadership style.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Furthermore, previous studies have shown that academic advisors characterized as empathetic, responsive, and helpful were more inclined to receive elevated ratings from students [21,22]. Likewise, our study indicates that academic advisors whom students perceived accessible, friendly, and empathetic to their academic needs were significantly more likely to receive positive reviews.…”
Section: Discussionsupporting
confidence: 74%